Genotypic and Phenotypic Diversity of Cryptococcus gattii VGII Clinical Isolates and Its Impact on Virulence - Barcellos, Vanessa A.; Martins, Liline M. S.; Fontes, Alide C. L.; Reuwsaat, Julia C. V.; Squizani, Eamim D.; de Sousa Araújo, Glauber R.; Frases, Susana; Staats, Charley C.; Schrank, Augusto; Kmetzsch, Livia; Vainstein, Marilene H. (Frontiers in Microbiology, 2018)
The Cryptococcus gattii species complex harbors the main etiological agents of cryptococcosis in immunocompetent patients. C. gattii molecular type VGII predominates in the north and northeastern regions of Brazil, leading to high morbidity and mortality rates. C. gattii VGII isolates have a strong clinical relevance and phenotypic variations. These phenotypic variations among C. gattii species complex isolates suggest that some strains are more virulent than others, but little information is available related to the pathogenic properties of those strains. In this study, we analyzed some virulence determinants of C. gattii VGII strains (CG01, CG02, and CG03) isolated from patients in the state of Piauí, Brazil. The C. gattii R265 VGIIa strain, which was isolated from the Vancouver outbreak, differed from C. gattii CG01, CG02 and CG03 isolates (also classified as VGII) when analyzed the capsular dimensions, melanin production, urease activity, as well as the glucuronoxylomannan (GXM) secretion. Those differences directly reflected in their virulence potential. In addition, CG02 displayed higher virulence compared to R265 (VGIIa) strain in a cryptococcal murine model of infection. Lastly, we examined the genotypic diversity of these strains through Multilocus Sequence Type (MLST) and one new subtype was described for the CG02 isolate. This study confirms the presence and the phenotypic and genotypic diversity of highly virulent strains in the Northeast region of Brazil.